Adjuvant therapy following induction therapy and surgery improves survival in N2‐positive non–small cell lung cancer. Issue 2 (1st December 2020) - White, Abby A.; Lee, Daniel N.; Mazzola, Emanuele; Kucukak, Suden; Polhemus, Emily; Jaklitsch, Michael T.; Mentzer, Steven J.; Wee, Jon O.; Bueno, Raphael; Swanson, Scott J.
Abstract: Background: The purpose of this study was to evaluate treatment strategies and factors influencing overall survival (OS) and disease‐free survival (DFS) in resectable, non–small cell lung cancer (NSCLC) with mediastinal (N2) lymph node metastasis. Methods: All patients undergoing surgery for NSCLC with N2 disease between 2006 and 2016 were included. Treatment approaches included surgery only, neoadjuvant therapy followed by surgery, surgery followed by adjuvant therapy, and neoadjuvant therapy followed by surgery and adjuvant therapy (triple therapy). Patient clinical and pathologic data were retrospectively collected. Results: A total of 281 patients were included in the study. In total, 209 patients had neoadjuvant therapy, 47.4% of which went on to received additional adjuvant therapy. The pathologic complete response rate was 12.9%. The treatment strategy which included triple therapy was isolated as a significant contributor to improved OS and DFS. Nodal downstaging (N0) after induction therapy conferred an OS benefit (38.3% vs. 15.6%, p  = .03). Patients with single‐station N2 disease experienced higher DFS. Video‐assisted thoracic surgery (VATS) lobectomy completion rates were higher at the end of the study period compared to the beginning ( p  < .001). Conclusions: Patients who undergo neoadjuvant therapy for N2‐positive NSCLC may benefit from additional adjuvant therapy. Single‐station N2 disease confers higher DFS. VATS completion rates for lobectomy increase as experience increases.